ANTIBACTERIAL EFFECTS OF 0.1% CHLORINE DIOXIDE ON ACTINOMYCES SP. AS AN AGENT OF BLACK STAIN - Eunike, Maria Clarissa; Fauziah, Eva; Suharsini, Margaretha (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to assess the antibacterial effects of 0.1% chlorine dioxide and 0.1% chlorhexidine mouthrinses on the bacterial viability of Actinomyces sp. as an agent of black stain. Methods: The authors conducted a clinical trial involving 16 children ages 6–11 with at least 8 black-stained teeth. Subjects were randomized into 2 groups and instructed to rinse with chlorine dioxide or chlorhexidine mouthrinse twice daily. At baseline and after 7 days, samples of black stain plaque were collected, and Actinomyces sp. was cultured. Its bacterial viability was evaluated using an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide assay. Results: After 7 days, Actinomyces sp. viability was remarkably reduced in both groups, and there was a significantly higher reduction in viability in the 0.1% chlorine dioxide group than there was in the 0.1% chlorhexidine group. Conclusion: Mouthrinse containing 0.1% chlorine dioxide has a greater antibacterial effect against Actinomyces sp. than mouthrinse containing 0.1% chlorhexidine.